The class reunion : an annotated translation and commentary on the Sumerian dialogue, Two scribes - Johnson, Justin Cale, 1971-; Geller, Markham J. (Cuneiform Monographs, 2015)
In The Class Reunion-An Annotated Translation and Commentary on the Sumerian Dialogue Two Scribes, J. Cale Johnson and Markham J. Geller present a critical edition, translation and commentary on the Sumerian scholastic dialogue otherwise known as Two Scribes, Streit zweier Schulabsolventen or Dialogue 1. The two protagonists, the Professor and the Bureaucrat, each ridicule their opponent in alternating speeches, while at the same time scoring points based on their detailed knowledge of Sumerian lexical and literary traditions. But they also represent the two social roles into which nearly all graduates of the Old Babylonian Tablet House typically gained entrance. So the dialogue also reflects on larger themes such as professional identity and the nature of scholastic activity in Mesopotamia in the Old Babylonian period (ca. 1800-1600 BCE).